2023
DOI: 10.1002/ece3.9869
|View full text |Cite
|
Sign up to set email alerts
|

Geographic isolation and environmental heterogeneity contribute to genetic differentiation in Cephalotaxus oliveri

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 128 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…In addition, we found a significant pattern of IBD for gene expression ( r = 0.657). Similarly, strong correlations between genetic distance and geographical distance were observed for EST‐SSR data ( r = 0.738; Liu et al, 2023) and SNP data ( r = 0.792). These results showed that studying expression variation patterns using transcriptome data is an important complementary approach to investigating population divergence.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, we found a significant pattern of IBD for gene expression ( r = 0.657). Similarly, strong correlations between genetic distance and geographical distance were observed for EST‐SSR data ( r = 0.738; Liu et al, 2023) and SNP data ( r = 0.792). These results showed that studying expression variation patterns using transcriptome data is an important complementary approach to investigating population divergence.…”
Section: Discussionmentioning
confidence: 68%
“…pringlei appears to be susceptible to the influence of environmental conditions, spatial autocorrelation, and even the interplay between both factors. Demographic history and gene flow processes might have been molded by distinct variations in their immediate environment, as has been suggested in other plants (Liu et al., 2023). Additionally, both neutral and adaptive data indicated the existence of induced spatial dependence, suggesting that geographical proximity may align with large‐scale environmental similarities (Borcard et al., 2011).…”
Section: Discussionmentioning
confidence: 82%
“…Finally, substantial variation remains unexplained, which is common in genetic studies using these methods (Gibson & Moyle, 2020; Liu et al., 2023). This could be attributed, in part, to the population structure that may not be fully explained by spatial variables of the MEM, potentially due to geographic heterogeneity present in the Mexican Transition Zone.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation-by‐distance (IBD) reveals that genetic differentiation among populations increases with geographic distance, while the isolation‐by‐environment (IBE) assumes a linear relationship between genetic variation and environmental differences among populations [ 77 ]. To explore the existence of IBD and IBE, we applied Mantel test to assess the relationships between genetic distance and geographic or environmental distance with R v4.3.2 ( https://www.r-project.org/ ).…”
Section: Methodsmentioning
confidence: 99%